BUSINESS SIGNIFICANCE OF EMPLOYEE VALUE PROPOSITION TOWARDS EFFECTIVE WORKFORCE MANAGEMENT - Avinash Pawar; Rira Nuradhawati; Atik Rochaeni; Indra Kristian (Universitas Jenderal Ahmad Yani, 2023)
The Employee Value Proposition (EVP) represents the perceived overall deal between employer and employee. The employer offers the employee and expects contributions from the employee in return. The inducements and contributions consist of mutual obligations and promises. Inducements typically concern career progression, organisational support, fair and transparent performance management and more tangible things such as pay and holiday entitlements. Contributions related to working hours, being an employer advocate within and outside the organisation, bringing skills, enthusiasm and entrepreneurship to productive work. Importantly, within the overall deal, nested deals are operating at different organisation levels, such as the tailored, workable arrangements forged between the team leader and team members. These reflect opportunities available for employees to shape their work experience. Top-performing companies create a sustainable EVP and total rewards strategy based on the needs, demographics and preferences of their workforce. Employee value Proposition refers to the rewards and benefits an employee receives in return for his performance at the organisation's workplace. The characteristics of the EVP need to be reflected in the corporate and employer brands. This paper takes reviews the concept of employee value proposition along with the business significance of human resource management.